Widening global variability in grassland biomass since the 1980s - MacDougall, Andrew S.; Esch, Ellen; Chen, Qingqing; Carroll, Oliver; Bonner, Colin; Ohlert, Timothy; Siewert, Matthias; Sulik, John; Schweiger, Anna K.; Borer, Elizabeth T.; Naidu, Dilip; Bagchi, Sumanta; et al. (Springer Nature, 2024)
Global change is associated with variable shifts in the annual production of aboveground plant biomass, suggesting localized sensitivities with unclear causal origins. Combining remotely sensed normalized difference vegetation index data since the 1980s with contemporary field data from 84 grasslands on 6 continents, we show a widening divergence in site-level biomass ranging from +51% to −34% globally. Biomass generally increased in warmer, wetter and species-rich sites with longer growing seasons and declined in species-poor arid areas. Phenological changes were widespread, revealing substantive transitions in grassland seasonal cycling. Grazing, nitrogen deposition and plant invasion were prevalent in some regions but did not predict overall trends. Grasslands are undergoing sizable changes in production, with implications for food security, biodiversity and carbon storage especially in arid regions where declines are accelerating.